HUBUNGAN SUPERVISI KEPALA SEKOLAH DENGAN ETOS KERJA PENDIDIK TAMAN KANAK-KANAK SE-KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Junita, Lismar; Novianti, Ria; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purposes of this research are: 1) To know how Supervision Principal around district Marpoyan Damai Pekanbaru City? 2) To know how the Working Educator's Educational Work ethic in Marpoyan Damai District of Pekanbaru? 3) To find out whether there is a Principal Supervision Relation with the work ethic of Kindergarten Educator in Marpoyan Damai around district, Pekanbaru? So it can be formulated the problem of this research are: 1) How Supervision Principal around district Marpoyan Damai Pekanbaru? 2) How is the Working Educator's Educational Work ethic in Marpoyan Damai Sub-district Pekanbaru? 3) Is there a Principal Supervision Relation with the work ethic of Kindergarten Educators in Marpoyan Damai Sub-district Pekanbaru City? This research was conducted in Kindergarten of Sub-district of Marpoyan Damai Pekanbaru City. This research is a correlation research. Population of this research is educator which exist in Kindergarten of Marpoyan Damai Sub-district of Pekanbaru Town which amounts to 196 educators. The sample in this study as many as 132 respondents are the kindergarten educators in the sub-district Marpoyan Damai Pekanbaru City. From the sample taken 20 people to be tested samples of research instruments and the rest of 132 people educators used as research samples. Based on the research results, it can be concluded: 1) Supervision Principal obtained percentage of 89.97% with Excellent category. 2) Educational Worker Educational Work ethic is obtained percentage of 61,37% with Good category. 3) There is a correlation between educators' perceptions of the principal's supervision with the work ethic of Kindergarten Teachers in Marpoyan Damai Sub-district, Pekanbaru City.Keywords: Supervision, Work Ethic